What´s new in the ISO 2789:2022 standard on international library statistics - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2023)
In September 2022, the sixth edition of the ISO 2789. Information and documentation. International library statistics standard was published, replacing ISO 2789:2013. This text analyzes the novelties introduced in this new version, which principally have to do with digital resources and services and with the incorporation of data on research support, as well as other aspects. The standard maintains practically the same structure as the previous edition, although the incorporation of an annex regarding the measurement of digital uses is emphasized. Numerous definitions reflecting the new reality of libraries are also added.